An 8-bit Digitally-controlled Low NF VGA for 5G Millimeter-wave Beamforming in 65 nm CMOS Technology - Sid Ahmed Tedjini; Sonia Salhi (ENP Engineering Science Journal)
In this paper, a linear-in-dB digitally controlled variable gain low-noise amplifier (D-VGLNA) designed in 65 nm CMOS process for the 5G mm-wave phase-array subsystem is presented. Based on the current steering technique, the designed 8-bit D-VGLNA achieves a gain range of 22 dB from -12 dB to +10 dB while it consumes 9.6 mW (without buffers). By boosting up the input transconductance thanks to a cross-coupled technique, the designed D-VGLNA achieves a noise figure of 2.3 dB, and 7 dB at maximum and 0 dB gain, respectively. It shows an input-output phase shift insensitivity to gain setting thanks to parasitic capacitance mitigation by holding the parasitic capacitance at common junction cascode transistor constant during gain setting. The DVGLNA returns a maximum of -6.5 dBm of 1dB compression point.